Effects of Surfactant Warm-Mix Additives on the Rheological Properties of High-Viscosity Asphalt - Jingtao Shi; Weiyu Fan; Yi Lin; Pinhui Zhao; Jian Ouyang (Advances in Materials Science and Engineering)
In order to evaluate the possibility of the application of warm mixing technology in high-viscosity asphalt mixture, in this paper, the effects of surfactant warm-mix additives (WMAs) on physical and rheological properties of high-viscosity asphalt (HVA) which was prepared with self-developed SBS/C9 petroleum resin blends (SPR) modifier were measured. The results indicate that the addition of WMA can decrease the viscosity and softening point but improve the penetration and ductility of warm-mix HVA. With the increase of the content of WMA, the modulus, failure temperature, viscosity, and recovery rate of warm-mix HVA all increased at first and then decreased, and the maximum value appeared when the modifier content was 1.0%–1.5%. Moreover, when the amount of WMA is 1.5%, the low-temperature performance of warm-mix HVA reaches the best value. Thus, the amount of WMA is of great importance for the warm-mix HVA, and in order to achieve ideal rheological properties, the recommended amount of WMA is 1.0%–1.5%. Considering economic improvement and environmental protection, WMA could be an alternative for increasing the workability of HVA.